2021
DOI: 10.3390/publications9020016
|View full text |Cite
|
Sign up to set email alerts
|

Conference Accreditation and Need of a Bibliometric Measure to Distinguish Predatory Conferences

Abstract: Academic conferences offer scientists the opportunity to share their findings and knowledge with other researchers. However, the number of conferences is rapidly increasing globally and many unsolicited e-mails are received from conference organizers. These e-mails take time for researchers to read and ascertain their legitimacy. Because not every conference is of high quality, there is a need for young researchers and scholars to recognize the so-called “predatory conferences” which make a profit from unsuspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Most (n=17) of the included papers were published between 2017 and 2021. The corresponding authors were from 12 different countries, where one-fourth were affiliated to the USA,24–28 followed by India,29–31 Denmark,32 33 Hungary,34 35 Saudi Arabia,36 Iran,37 UK,38 Australia,39 Switzerland,40 Canada,41 Hong Kong42 and the Czech Republic 43. PC attract multidisciplinary attention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most (n=17) of the included papers were published between 2017 and 2021. The corresponding authors were from 12 different countries, where one-fourth were affiliated to the USA,24–28 followed by India,29–31 Denmark,32 33 Hungary,34 35 Saudi Arabia,36 Iran,37 UK,38 Australia,39 Switzerland,40 Canada,41 Hong Kong42 and the Czech Republic 43. PC attract multidisciplinary attention.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies collected empirical data,25 26 28 34–36 38 40–43 where one half used a quantitative approach, one qualitative. Nine papers were theoretical,24 27 29–33 37 39 All papers were peer reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of quality in peer reviewing is an indicator of the predatory behavior of some publishers or conference organizers [42][43][44]. Makvandi et al [45] suggested establishing a system for evaluating the quality of scientific conferences. Like scientific journals, it is difficult to cover every global scientific conference with an appropriate evaluation system.…”
Section: Discussionmentioning
confidence: 99%